Identifikasi Identitas Merek dan Implementasi Komunikasi Pemasaran di Pasar Musik Indonesia - Kevin Valeryan; Siti Nurjanah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study will discuss the impact of digitalization on music marketing. With the emerging means for online music distribution, there has been a major shift in the music industry as a whole. The distribution resulted in a flood of new music and artists being marketed every day, resulting in oversaturation in the market. With a very significant change in the quantity and means of distribution of music, marketing efforts shifted focus from offline sales and the focus on selling the music itself, to strengthening brand identity of the artist. This study aims to determine the implementation of marketing communications and also how to form brand identities for musicians and music labels that can be implemented in the Indonesian music market. This research was conducted using a qualitative method with triangulation analysis of literature review, observation, and interviews with five informants, namely, music managers and observers in order to collect information from various points of view, implement marketing communications, and find out and build brand identity. Based on the results of data analysis, it is known that the music industry in Indonesia is divided into two, namely major labels and independent labels. The importance of building an identity is to be able to target the market, as well as to position the brand, and the main factor in creating a distinctive image in the eyes of consumers. Due to the diversity and variety of the music industry, now, a brand or an artist must have a Unique Selling Point, because this can be a differentiating aspect between one artist to another. The implementation of integrated marketing communications used by the music industry on both labels (major label and independent label) is carried out using social media as the main tool in promoting the brand and its marketing activities.